2018
DOI: 10.1111/btp.12541
|View full text |Cite
|
Sign up to set email alerts
|

Flooding and soil composition determine beta diversity of lowland forests in Northern South America

Abstract: Beta diversity may be determined by dispersal limitation, environment, and phylogeographic history. Our objective was to advance the understanding of plant species turnover in rain forests in northern South America and determine which factors are affecting species beta diversity. We evaluated the relative effect of environmental variables (i.e., soil, climate, fragmentation, and flooding frequency) and dispersal limitation (i.e., geographical distance and resistance distance due mountain barriers) on tree beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 57 publications
3
23
0
1
Order By: Relevance
“…Nuestros resultados apoyan la hipótesis general de que la composición florística de los bosques tropicales está relacionada con los nutrientes del suelo. Si bien esto se ha demostrado en bosques amazónicos y en Panamá (Poulsen et al, 2006;Kristiansen et al, 2012;Garibaldi, Nieto-Ariza, Macía, & Cayuela, 2014;Tuomisto et al, 2014;Stevenson et al, 2018;Muscarella et al, 2018), nuestro estudio es el primero en resaltar que, en las tierras bajas del Chocó, la composición de las comunidades de palmas está relacionada con los nutrientes: los suelos con concentraciones bajas en bases intercambiables son más ricos en especies.…”
Section: Discussionunclassified
“…Nuestros resultados apoyan la hipótesis general de que la composición florística de los bosques tropicales está relacionada con los nutrientes del suelo. Si bien esto se ha demostrado en bosques amazónicos y en Panamá (Poulsen et al, 2006;Kristiansen et al, 2012;Garibaldi, Nieto-Ariza, Macía, & Cayuela, 2014;Tuomisto et al, 2014;Stevenson et al, 2018;Muscarella et al, 2018), nuestro estudio es el primero en resaltar que, en las tierras bajas del Chocó, la composición de las comunidades de palmas está relacionada con los nutrientes: los suelos con concentraciones bajas en bases intercambiables son más ricos en especies.…”
Section: Discussionunclassified
“…Seasonally flooded forests (SFF) perform key ecosystem functions such as water retention, cation exchange, the balance of nutrient cycle, and microclimate; these functions are associated with particular plant communities, which have a narrow regeneration niche [2]. Additionally, organic matter and sediments in the soil largely determine the ecological dynamics of their tree communities [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the importance of TFF for various primate species in Colombia, as well as the relationship between ecological integrity and the viability of associated primates [5][6][7]. Likewise, TFF of the Colombian Orinoco (especially in the Department of Meta), are considered key in the transition between the Andes and the Amazon [3,8]. Floristically, SFF are less diverse than TFF due to the ecophysiological challenges associated with floods [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The varying patterns of plant community assembly across environmental gradients have inspired important ecological concepts and have been a recurring subject of research since the earliest ecological studies (Clements 1936;Keddy 1992;Laliberté et al 2014;Whittaker 1956), and there is increasing interest in understanding plant community assembly in light of ongoing global environmental changes (Lewthwaite et al 2017). The effects of larger-scale geographic gradients in water availability on community composition and species richness have been demonstrated in a wide range of ecosystems, from tropical forests (Esquivel-Muelbert et al 2017;Pyke et al 2001) and seasonally dry ecosystems (Scholes et al 2002) to riparian forests (Garssen et al 2015) and floodplains (Casanova and Brock 2000;McGinness et al 2018;Stevenson et al 2018). In addition, local variation in hydrological regime can shape plant community composition at individual sites (Araya et al 2011;Kirkman et al 2001;Silvertown et al 1999), which has led researchers to define distinct hydrological niches for different species (Silvertown et al 2015).…”
Section: Introductionmentioning
confidence: 99%